Relationship between Attachment Style and Empathy in Nursing Students - Khodabakhsh MR (Iran University of Medical Sciences, 2012)
Background & Aims : Attachment styles of nurses as caregivers and members of healthcare teams and empathy as individuals' basic capacity which contributes to the management of relationships, the supporting of communal activities, and insight to the quality of nurse-patient relationship are therefore considered to be an important topic worth studying. This study examined the relationship between attachment styles and empathy in nursing students living in dormitories of Tehran University of Medical Sciences .   Material & Method : A sample of 260 university students (130 males, 130 females) participated in this study. All participants completed the Attachment Style Questionnaire (ASQ), and the Interpersonal Reactivity Index (IRI). Data was collected and analyzed using Pearson correlation coefficient and regression analysis using SPSS (v.18)   Results : The results showed that secure and insecure attachment styles had significant positive and negative correlation with empathy, respectively. The results of regression analysis revealed that secure attachment style is shown to be the predicting 67% of the variance of empathy variable whereas anxiety attachment styles is shown to be the predicting 61% and avoidant attachment styles is shown to be the predicting 54% of the variance of empathy variable.  Conclusion : Assessing attachment styles and relationship of attachment styles with empathy can be valuable guidelines in order to provide mental health for nursing students . The meaning and limitation of this study and the suggestion for the further study are discussed.  Received: 2 Jun 2012   Accepted: 27 Aug 2012